Situational Awareness of Opioid Consumption: The Missing Link to Reducing Dependence After Surgery?. (2nd February 2022) - Engelman, Daniel T.; Crisafi, Cheryl; Hodle, Taylor; Stiles, John; Nathanson, Brian H.; Zarbock, Alexander; Grant, Michael C.
Abstract : A tool for collecting and analyzing morphine milligram equivalents (MMEs) can be used to overcome barriers to situational awareness around opioid utilization in the setting of multimodal pain management. Our software application (App) has facilitated data collection, analysis, and benchmarking in a manner that is not logistically feasible using manual methods. Real-time postoperative tracking of MME over the course of an episode of care can be prohibitively labor-intensive, and teams must have practical strategies to overcome this obstacle. In view of the link between the magnitude of opioid prescriptions at discharge and persistent opioid use after cardiac surgery, we believe that improving situational awareness among the patient care team is a vital first step in reducing opioid dependence after cardiac surgery.